Client perspectives on creating supportive sexual health environments for people with persistent anxiety: a qualitative study - Mark Gilbert; Travis Salway; Stéphanie Black; Sarah Watt; Aidan Ablona; Hsiu-Ju Chang; Heather Nicole Pedersen (BMJ Public Health)
Objectives We sought to explore sexual health service clients’ perspectives, preferences and suggestions for how to better address or alleviate anxiety among clients of sexual health services (eg, sexually transmitted infection testing) regarding both online and in-person sexual health services among those who experience persistent anxiety.Methods We conducted qualitative interviews with 27 sexual health service clients with persistent experiences of anxiety in British Columbia, Canada. Participants were recruited from respondents to a COVID-19-related sexual health survey who consented to follow up. Interviews were conducted via Zoom, recorded and transcribed. Transcripts were coded and analysed using thematic analysis by searching for themes in order to summarise the experiences and needs of participants.Results The median participant age was 34. 16 participants identified as women, 10 as men and 1 each as non-binary and gender fluid. Participants described anxiety related to sexual health service access and experiences due to sexual health-related stigma and privacy concerns; provider judgement and lack of communication or information regarding test results. They suggested that routinely integrating discussions with providers about mental health in sexually transmitted and bloodborne infection (STBBI) testing appointments may help clients feel safer and could connect them to support. They highlighted the need for personal and genuine interactions with providers (eg, making appointments feel less perfunctory, asking clients how they are feeling about why they are there) and sufficient time with providers (eg, not feeling rushed through the appointment, time to discuss resources, testing and advice).Conclusions Disease-specialised health services may not adequately address the multifaceted and inter-related mental health needs of people accessing services. In STBBI testing service settings, more personalised appointments, additional communication with providers and easier access to results can help improve both the service experiences of people experiencing persistent anxiety and their connections to appropriate mental health support.